Teknologi Produksi Kubis Organik di Desa Serang Kecamatan Karangreja, Kabupaten Purbalingga - Sarjito, Agus; Farid, Noor; Indaryanto, Budi Supono (ABDIPRAJA (Jurnal Pengabdian kepada Masyarakat), 2023)
An extension activity has been carried out in order to develop organically sound cabbage cultivation. This agricultural extension aimed to improve farmer’s skills in controlling major pests and diseases on cabbage crops; to enhance farmer’s skills in making tricho-compost; to enhance quantity and quality of cabbage yields so as to increase farmer's income. This agricultural extension program is carried out through: training, mentoring, and demonstration plots. Pre-Test and Posttest were used to evaluate the success of the training. Farmers' knowledge increases after participating in training and practice in the field. The results of this activity showed that the participating farmers were able to practice organic cabbage cultivation well. Both farmer groups were able to apply methods of organically pest control and obtained high yields. The Margo Sayur Farmer Group obtained a cabbage yield of 19,74 tons per hectare, while the Ngudi Sayur Group obtained a yield of 18,79 tons per hectare.Key words: organic cabbage, organic fertilizer, botanical and biological pesticide, and yield.